2020
DOI: 10.15567/mljekarstvo.2020.0204
|View full text |Cite
|
Sign up to set email alerts
|

Associations between milking technology, herd size and milk production parameters on commercial dairy cattle farms

Abstract: The aim of the study was to survey the milking technology and to analyse the associations between milking parlour type, herd size, and milk production parameters on dairy cattle farms. The milking technology was surveyed by using a questionnaire in 417 Hungarian dairy herds with 177,514 cows in 2017, and it was compared with their official farm milk production data. The surveyed farms were categorized according to their size (1-50, 51-300, 301-600, and >600 cows) and to their milking parlour types (herr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The prevailing loose housing dairy farms mostly used two technologies: herringbone and rotary milking parlors (Priekulis and Kurgs, 2010). Nevertheless, in Hungary, the most commonly used type of milking parlors was the herringbone (71.0%), followed by the parallel (14.9%), rotary (9.6%), and others (4.6%) (Ivanyos et al, 2020), which distribution was found by this study, as well.…”
Section: Milking Equipmentsupporting
confidence: 78%
See 2 more Smart Citations
“…The prevailing loose housing dairy farms mostly used two technologies: herringbone and rotary milking parlors (Priekulis and Kurgs, 2010). Nevertheless, in Hungary, the most commonly used type of milking parlors was the herringbone (71.0%), followed by the parallel (14.9%), rotary (9.6%), and others (4.6%) (Ivanyos et al, 2020), which distribution was found by this study, as well.…”
Section: Milking Equipmentsupporting
confidence: 78%
“…Nipers et al (2016) recommended a separate parlor for 200 cows. However, the Hungarian farms with a smaller number of cows had already used separate milking parlors (Ivanyos et al, 2020). The prevailing loose housing dairy farms mostly used two technologies: herringbone and rotary milking parlors (Priekulis and Kurgs, 2010).…”
Section: Milking Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, the milk ejection rate is the most vital sign of cows' suitability for machine milking, which depends on several factors: reflex perception of machine milking, hormonal regulation of milk ejection, udder morphology, type of highest nervous activity, and others. The rate of milk ejection indicates not so much the time of milking animals, as the prerequisites for a positive reflex perception of milking, easy filling udder with milk before milking, as well as readiness for repeated milking with a high shutdown threshold of milking machine (Ivanyos et al, 2020;Mantysaari et al 2019;Palii et al, 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the intensity of milk ejection determines the cost of labor and time to obtain one quintal of milk. Therefore, this indicator's improvement provides a tremendous economic effect (Ivanyos et al, 2020). It is necessary to select an equivalent milk ejection reflex to remove a significant portion of the produced milk from the animal's udder.…”
Section: Introductionmentioning
confidence: 99%